Forensic epistemology: testing the reasoning skills of crime scene experts. Issue 4 (2nd October 2019) - Illes, Mike; Wilson, Paul; Bruce, Cathy
Abstract: In recent years, crime scene analysis has been transitioning from being a technical discipline to being a scientific process. This progression is shifting the forensic practitioner examining crime scenes into a deeper level of scientific reasoning. This study evaluates the use of reasoning by practitioners in the disciplines of crime scene investigations and bloodstain pattern analysis. A well-established classroom test of scientific reasoning (CTSR) was distributed online to active crime scene investigators (CSI) and bloodstain pattern analysts (BPA) (n = 213) using Qualtrics software. The survey provides quantitative data on the reasoning ability of the participating practitioners along with demographic information on education, employment status (specifically, police or civilian), and work experience. Linear regression analyses indicate that there is a significant difference between the CTSR scores and education level. The higher educated practitioner (graduate level) performed better on the reasoning test. No significant differences were found between the test scores and the years of experience, even when sectioned into 5-year increments of 5 to 25+ years of experience. Similarly, there was no difference between the test scores and employment status for the CSI group and within the BPA group. This information suggests that the level of education plays the most important role in the development and use of reasoning skills, whereas experience and employment status are not as influential. The test scores were also mapped to Piaget's categories – concrete operational, transitional and formal operational reasoners – with 69.5% of CSI and 77% of BPA scoring as formal operational reasoners. The authors recommend that a CTSR be used for testing current and future (tertiary forensic students) practitioners for evaluating reasoning skills and identifying scientific learning gaps. This study also supports further research into forensic epistemology and pedagogy, to deepen our knowledge of science in forensic science.